Current imaging practice for suspected scaphoid fracture in patients with normal initial radiographs: UK-wide national audit. Issue 6 (June 2019) - Chunara, M.H.; McLeavy, C.M.; Kesavanarayanan, V.; Paton, D.; Ganguly, A.
Abstract : AIM: To assess the current practice of scaphoid fracture imaging (where initial scaphoid radiographs are normal) in the UK. MATERIALS AND METHODS: A survey monkey questionnaire was sent to 140 eligible NHS trusts derived from the NHS England database following exclusion of all non-acute and specialist centres. Four questions were asked regarding the provision of magnetic resonance imaging (MRI) for radiographically occult scaphoid fractures, time to MRI, number of departmental MRI scanners, and alternative imaging offered. RESULTS: Responses were received from 74 trusts (53%). Thirty-eight offered MRI as a first-line test in plain-film occult scaphoid injury, 25 preferred computed tomography (CT), and 11 opted for repeat plain radiographs. Of the 38 trusts who offered MRI, 26 provided this within 1 week; the rest within 2 weeks. No trends were identified based on the size of the hospital or its geographical location. Statistical analysis of the data revealed no significant relationship between the number of MRI scanners and the provision of MRI, nor between the numbers of MRI scanners and the time to MRI. CONCLUSIONS: MRI has been recognised in the literature as a highly specific, highly sensitive, and cost-effective tool, yet only 51% of trusts provide this service in the UK. For those who cannot offer MRI first-line, CT remains a very accurate and reliable alternative. Highlights: 51% of trusts provide MR for x-ray occult scaphoid fractures. 68% provide MR within 1 week, 100% within 2 weeks. No statistical significance between no° of MR scanners and MR provision. No statistical significance between no° of MR scanners and time-to-MRI. Where MR not offered, 34% use CT and 15% rely on repeat radiographs.